Prueba de resistencia al golpeo en boxeadores juveniles de alta calificación. Análisis según pesos corporales - Herrera Quevedo, J.; Almenares Pujadas, M. E.; Nicot Balón, R. G.; Horta Dominguez, H. (Revista Cubana de medicina del deporte y la cultura fisica, 2018)
Biomedical tests are required to identify the characteristics of sports performance in relation to the specific physical training of the boxer. Material and methods. A descriptive study was carried out with the first figures of National Youth Boxing Preselection, taking as a working protocol the beating test applied by the coaches in the systematic pedagogical evaluation of these athletes. Results: The realized work consisted of 729 ± 181 strokes (light 717 ± 157, medium 747 ± 231 and heavy 72 3 ± 159), with significant differences between rounds (p = 0.001). Heart rate pre and post test were 82.6 ± 6.0 bpm and 195 ± 7.6 bpm, with pre and post significant differences between weight groups (p = 0.01). Lactacidemia pre and post load were 2.70 ± 1.2 mmol / L and 12.2 ± 2.60 mmol / L with significant increases (p = 0.001). Conclusion. Results of this preliminary version of test, shows the convenience of its improvement and application for the orientation and reorientation of the boxers special preparation.